PERSEPSI GURU TERHADAP APLIKASI EDMODO SEBAGAI ALAT BANTU KEGIATAN BELAJAR DI SEKOLAH DASAR - Novita Wisudawati; Eko Kuntarto; Agung Rimba Kurniawan (Universitas Muhammadiyah Makassar, 2020)
The purpose of this study is to describea how the teacher's perception of the application of Edmodo as a tool for learning activities in Al-Falah Islamic Elementary School Jambi. This research is a study that uses a qualitative approach to the type of phenomenological research. Researchers chose a qualitative approach to the type of phenomenological research because researchers wanted to examine according to phenomena related to teacher perceptions of the application of edmodo as a learning aid in the Al-Falah Islamic Elementary School in Jambi. The informants of this study were nine Al-Falah Jambi Islamic elementary school teachers. Researchers took the